Commercial thinning effects on growth, yield and mortality in natural lodgepole pine stands in Alberta - Sanatan Das Gupta; Bradley D. Pinno; Tim McCready (The Forestry Chronicle)
There is an expected decrease in the short to mid-term timber supply of lodgepole pine (Pinus contorta var. latifolia) in Alberta, Canada due to the impacts of past fires and the mountain pine beetle outbreak. Commercial thinning is a potential option for increasing mid-term sawlog timber supply by decreasing the time needed for individual trees to reach merchantable size, through providing access to fiber earlier in the rotation, and from the ability to keep mature stands on the stump longer. In the current study, we evaluated the effects of commercial thinning in stands of different ages. Stands less than 70 years old at thinning were classified as commercial thinning (CT), whereas stands greater than 70 years at thinning were classified as salvage thinning (ST). Tree growth and survival were measured every five years from 1996 to 2016 in both thinned and unthinned stands. Fifteen years post-thinning, stand volume was less in the thinned stands relative to the unthinned controls. However, when volume removed at thinning was considered, volume gain from thinned stands was greater than that from the controls in both thinning treatments. Individual tree DBH and live crown ratio were also greater in thinned stands relative to controls. Thinning favored diameter gain mostly in the medium-sized trees in CT but both small to medium-sized trees in ST. Thinning reduced mortality in all stands relative to the controls and a maximum of 50% reduction in mortality was observed in CT. Overall, the findings suggest that natural lodgepole pine stands may respond to commercial thinning with a net gain in cumulative volume at final harvest.